Basic Concepts Of Internalizing National Insights In SMAN 9 Malang City - Moh Wahyu Kurniawan (Universitas of Muhammadiyah Makassar, 2021)
National insight is a way of looking at the nation based on self-awareness as citizens of various ethnic differences, customs, regions, and unity in achieving national goals. This study aims to analyze the basic concepts of nationalism in SMA Negeri 9 Malang. The type of research isqualitative, data sources in this study using primary data and secondary data. The data collection techniques in this study used observation, interviews and documentation. The analysis in this study uses Miles Huberman. The results of the study show the following. (1) increasing national insight in SMA Negeri 9 Malang, namely through learning in the classroom, especially in Civics subjects; (2) Through extracurricular and co-curricular activities including Scouting activities which are attended by tenth grade students, Paskibraka, Nature Lovers Students (SPA), Traditional Dance, and Social Sinau which are mandatory programs by students which are carried out for 3 days in the planned village . This activity equips students to form national character by taking the values that exist in society (3) Through school culture. This includes flag ceremonies that are carried out regularly as a form of creating a sense of love for the homeland and increasing students' national insight about the values of nationalism, singing nationalism songs before carrying out learning activities, and school literacy movements. Wawasan kebangsaan merupakan cara pandang terhadap bangsa yang dilandasi kesadaran diri sebagai warga negara akan bermacam-macam perbedaan suku, adat istiadat, wilayah, serta kesatuan dalam mencapai tujuan nasional. Penelitian ini bertujuan untuk menganalisis konsep dasar wawasan kebangsaan di SMA Negeri 9 Malang. Jenis penelitian adalah kualitatif, data sumberdata dalam penelitian ini menggunakan data primer dan data sekunder. Adapun teknik pengumpulan data dalam penelitian ini menggunakan observasi, wawancara dan dokumentasi. Analisis dalam penelitian menggunakan Miles Huberman. Hasil penelitian menunjukkan sebagai berikut. (1) peningkatan wawasan kebangsaan di SMA Negeri 9 Malang yakni dengan melalui pembelejaan didalam kelas khususnya di mata pelajaran PPKn; (2) Melalui kegiatan ektrakulikuler dan ko-kulikuler meliputi kegiatan Pramuka yang diikuti oleh siswa disekolah kelas sepuluh, Paskibraka, Siswa Pencinta Alam (SPA), Tari Tradisional, dan Sinau Sosial yang merupakan program wajib oleh siswa yang dilaksanakan 3 hari didesa yang telah direncanakan. Kegiatan ini membekali siswa untuk membentuk karakter kebangsaan dengan mengambil nilai-nilai yang ada di masyaraka (3) Melalui budaya sekolah. Meliputi upacara bendera yang dilakukan secara rutin sebagai wujud menciptakan rasa cinta tanah air dan meningkatkan wawasan kebangsaan siswa tentang nilai nilai nasionalisme, menyanyikan lagu nasionalisme sebelum melakukan kegiatan pembelajaran, dan gerakan literasi sekolah.